2008
DOI: 10.1186/1471-2296-9-30
|View full text |Cite
|
Sign up to set email alerts
|

Functional illness in primary care: dysfunction versus disease

Abstract: Background: The Biopsychosocial Model aims to integrate the biological, psychological and social components of illness, but integration is difficult in practice, particularly when patients consult with medically unexplained physical symptoms or functional illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Engel's model has been described as 'abstract' (56), and'… lacking operationalisation… ' (57). It has also been suggested that it is difficult for clinicians to deviate from an injury or disease-based model (56). There are numerous factors that impact physical therapists' ability to integrate psychosocial elements into treatment, one being the absence of a model that represents the domain's scope in a detailed and digestible format.…”
Section: Facilitating Application Of Holistic Perspectivesmentioning
confidence: 99%
“…Engel's model has been described as 'abstract' (56), and'… lacking operationalisation… ' (57). It has also been suggested that it is difficult for clinicians to deviate from an injury or disease-based model (56). There are numerous factors that impact physical therapists' ability to integrate psychosocial elements into treatment, one being the absence of a model that represents the domain's scope in a detailed and digestible format.…”
Section: Facilitating Application Of Holistic Perspectivesmentioning
confidence: 99%
“…But our primary care colleagues can take the idea further. In a thought-provoking paper, Williams et al 6 show that dysfunction is alive, and troublesome, in so many disciplines -whether gastroenterology, psychiatry, psychology, etc. They suggest that rather than classifying our patients' problems by body systems, classification between dysfunction and disease is just as important.…”
Section: Bravo Dysfunction!mentioning
confidence: 98%
“…104 We have previously proposed a classification of illness that includes orthogonal dimensions of pathology and dysfunction. 105 For this purpose, pathology is narrowly defined as pathological processes that cause gross or microscopic structural change that may, but not necessarily, result in disturbance of function. Dysfunction, by contrast, is abnormal functioning of the body, caused by, or manifested as, disturbed physiological or psychological processes independent of known structural pathology (Fig.…”
Section: Relationship Between Pathology and Dysfunctionmentioning
confidence: 99%